2007
DOI: 10.1152/ajpcell.00215.2007
|View full text |Cite
|
Sign up to set email alerts
|

In vivo leukocyte labeling with intravenous ferumoxides/protamine sulfate complex and in vitro characterization for cellular magnetic resonance imaging

Abstract: Wu YJ, Muldoon LL, Varallyay C, Markwardt S, Jones RE, Neuwelt EA. In vivo leukocyte labeling with intravenous ferumoxides/protamine sulfate complex and in vitro characterization for cellular magnetic resonance imaging. Am J Physiol Cell Physiol 293: C1698-C1708, 2007. First published September 26, 2007; doi:10.1152/ajpcell.00215.2007.-Cellular labeling with ferumoxides (Feridex IV) superparamagnetic iron oxide nanoparticles can be used to monitor cells in vivo by MRI. The objective of this study was to use h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 48 publications
6
59
1
Order By: Relevance
“…The NP of SPIO and NF preparations were different in surface morphology, physical characteristics (density), surface charge, PEG concentration and functional modification which may affect the PK. The cellular and tissue uptake was effected by several characteristics of the nanoparticles e.g., particle size, coatings, and charge as demonstrated by Wu et al, (30). In another study surface properties had a larger impact on cellular uptake of SPIO particles rather than particle size (31).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The NP of SPIO and NF preparations were different in surface morphology, physical characteristics (density), surface charge, PEG concentration and functional modification which may affect the PK. The cellular and tissue uptake was effected by several characteristics of the nanoparticles e.g., particle size, coatings, and charge as demonstrated by Wu et al, (30). In another study surface properties had a larger impact on cellular uptake of SPIO particles rather than particle size (31).…”
Section: Discussionmentioning
confidence: 84%
“…Each purified RINP was a dark brown, homogeneous suspension and remained at the origin of PAGE. The RINPs (20,30 and 100 nm) shown in figure 2A, by Coomassie lanes 1− 3 and radioactivity in lanes 4 −6, did not migrate due to the high molecular weight. However, no unbound ChL6 or 111 In-DOTA-ChL6 was observed, corresponding to the control protein in Figure 2A Figure 3 shows the evaluation of the RINP mobility by CAE at 11 min (lanes # 1, 3 and 5) and 45 min (lanes # 2, 4 and 6).…”
Section: Preparation Characterization and Quality Assurance Of Ric mentioning
confidence: 92%
“…First, the labeling efficiency of neutrally charged USPIO (Sinerem/Combidex) in monocytes is considered to be rather poor as demonstrated in several in vitro and in vivo studies [18,22,46,47,48]. Conversely, the labeling of circulating leukocytes has been shown to significantly increase after intravenous injection of an SPIO/transfection agent (Feridex/protamine sulfate) complex [48]. Furthermore, monocytes are known to favor the uptake of larger nanoparticles, such as Endorem/Feridex, or charged nanoparticles, such as Resovist [47].…”
Section: Cellular Mri Of Leukocytesmentioning
confidence: 99%
“…Currently, Feraheme is only clinically approved for the treatment of iron deficiency anemia in adult patients with chronic kidney disease. However, several studies have shown that Feraheme can also be employed as a contrast agent for MRI [48,53,54,55]. Another alternative is P904 (Guerbet), 25- to 30-nm iron oxide particles for which phase I clinical trials have been initiated.…”
Section: Cellular Mri Of Leukocytesmentioning
confidence: 99%
“…With the nano-scaled sizes and non-toxicity, magnetic nanoparticles are applied to bio-medicine, such as magnetic resonance imaging (MRI) contrast agent [1][2][3][4], drug delivery [5][6][7], cell sorting [8,9], etc. Since 1997, researchers have been proposing to use bio-functionalized magnetic nanoparticles for immunoassay.…”
Section: Introductionmentioning
confidence: 99%